They ask you answer : a revolutionary approach to inbound sales, content marketing, and today's digital consumer - Sheridan, Marcus (Hoboken : Wiley, 2017)
"A revolutionary marketing strategy proven to drive sales and growth They Ask You Answer is a straightforward guide to fixing your current marketing strategy. Regardless of your budget, you are almost certainly overspending on television, radio, and print ads, yet neglecting the number-one resource you have at your disposal: the Internet. Content marketing is no longer about keyword-stuffing and link-building; in fact, using those tactics today gets your page shuffled to the bottom of the heap. Quality content is the key to success, and you already have the ingredients in-house. This book shows you how to structure an effective content strategy using the same proven principles that have revolutionized marketing for all types of businesses, across industries. Author Marcus Sheridan's pool company struggled after the housing collapse; today, they're one of the largest pool installers in the U.S., turning away millions of dollars in business they simply cannot accommodate every year. How did he manage it? He answered questions. This book shows you how Marcus's strategy can work for your business, and how to use your keyboard to bring customers through the door. Boost your company's web presence with methods that work Build a level of trust that generates customer evangelism Leverage your in-house resources to produce winning content Utilize tactics that work, regardless of industry or sector When people have questions, they ask a search engine. If you have answers, the right content strategy will get them to the top of the search results and seen by millions of eyes every day. Drop the marketing-speak, stop "selling," and start answering. Be seen as an authority, not just another advertisement. They Ask You Answer describes a fresh approach to marketing and the beginning of big things for your business"--
"This book will not just tell the incredibly practical and extraordinarily simple story of River Pools and Spas, but it will also dissect how other companies of various industries have managed to find exceptional results applying these same principles, making it relatable to all industries, businesses, and entrepreneurs alike"--
Includes index.
Keywords: Marketing; Sales promotion